Effects of whole-body electromyostimulation training on upper limb muscles strength and body composition in moderately trained males: A randomized controlled study - Qin, Yin; Chen, Hui; Liu, Xiaoying; Wu, Jiwei; Zhang, Yinxin (Frontiers in Public Health, 2022)
Resistance training has been known to have a positive effect on muscle performance in exercisers. Whole-body electromyostimulation (WB-EMS) is advertised as a smooth, time-efficient, and highly individualized resistance training technology. The purpose of this study is to evaluate the effects of WB-EMS training on maximum isometric elbow muscle strength and body composition in moderately trained males in comparison to traditional resistance training. The study was a randomized controlled single-blind trial. Twenty, moderately trained, male participants (25.15 ± 3.84, years) were randomly assigned to the following groups: a WB-EMS training group (n = 11) and a traditional resistance training group (the control group ([CG]: n = 9). Both training intervention programs consisted of 18 training sessions for six consecutive weeks. All subjects performed dynamic movements with the WB-EMS or external weights (CG). The primary outcome variables included maximum isometric elbow flexor strength (MIEFS), maximum isometric elbow extensor strength (MIEES) and surface electromyography amplitude (sEMGRMS). Secondary outcomes involved lean body mass, body fat content, arm fat mass, and arm lean mass. ANOVAs, Friedman test and post hoc t-tests were used (P = 0.05) to analyze the variables development after the 6-week intervention between the groups. Significant time × group interactions for MIEFS (η2 = 0.296, PBonferroni = 0.013) were observed, the increase in the WB-EMS group were significantly superior to the CG (23.49 ± 6.48% vs. 17.01 ± 4.36%; MD [95%CI] = 6.48 [1.16, 11.80]; d = 1.173, P = 0.020). There were no significant differences were observed between interventions regarding MIEES, sEMGRMS and body composition. These findings indicate that in moderately trained males the effects of WB-EMS were similar to a traditional resistance training, with the only exception of a significantly greater increase in elbow flexor strength. WB-EMS can be considered as an effective exercise addition for moderately trained males.